Participatory action research, social networks, and gender influence soil fertility management in Tanzania - Mponela, Powell; Manda, Julius; Kinyua, Michael; Kihara, Job Maguta (Springer, 2023)
Transformation of knowledge systems and fostering learning among smallholder farmers such as through participatory action research (PAR) is key to agricultural growth in rural sub-Saharan Africa. We investigate how PAR influences uptake/use of integrated soil fertility management (ISFM) while accounting for gendered, bonding and bridging social capital. Stratified by engagement in a mother-baby PAR and by resource endowments, 607 smallholder farmers were sampled from northern Tanzania. Binary logistic and multinomial logit models revealed that full engagement in PAR was associated with early adoption of inorganic fertilizers, either as a dichotomous decision or an ISFM bundle with improved varieties, organic matter inputs and soil and water conservation. Bonding social capital through cooperatives, farmer groups, and farmer-farmer local networks supports soil and water conservation, especially among resource-poor farmers. Among the high-resource farmers, increased women’s bargaining power in farm input purchases supports fertilizer and manure use while increased bargaining power in livestock tending supports crop residue incorporation. ISFM usage is constrained by age of decision-makers and a higher number of dependents per worker while education level and farm sizes increase its likelihood. In the resource-constrained, with low extension and technical support, and men-dominated patrilineal farming systems of Africa, the study places PAR, social networks, and gender inclusivity as key approaches for improving smallholder’ ISFM.